Neolithic pastoralism and plant community interactions at high altitudes of the Pyrenees, southern Europe - Irene Julián-Posada; Graciela Gil-Romera; Sandra Garcés-Pastor; Peter D. Heintzman; Daniel Gómez; Federico Fillat; Ana Moreno; Javier Lara-Recuero; Pere Bover; Lourdes Montes; Alejandro Sierra; Blas Valero-Garcés; et al. (Communications Earth & Environment)
Abstract The Neolithization process introduced remarkable ecological impacts, especially in Mediterranean mountain areas. We generated a comprehensive sedimentary ancient DNA record from the central Pyrenees, spanning 12,200 to 1300 years before present, revealing the earliest continuous presence of sheep (6500 years before present) and cattle (5900 years before present) in alpine southern Europe. This evidence suggests pastoralism nearly concurred with the Neolithic in the Iberian lowlands, challenging prior assumptions of only sporadic occurrence and confirming Neolithic pastoralist use of mountain ecosystems. A notable plant community shift arose at 6000 years before present, with deciduous forests transitioning into diverse open grasslands. This change became pronounced at 4200 years before present, aligning with continuous presence of domesticates and a regional cooling climate, suggesting a synergistic relationship between past climate change and human-induced plant community alteration. These findings highlight complex interactions between climate, human activities, and landscape dynamics during the Neolithic in Mediterranean mountains.